A novel promising infrared nonlinear optical selenide KAg3Ga8Se14 designed from benchmark AgGaQ2 (Q = S, Se). Issue 9 (7th January 2021) - Li, Jia-Nuo; Yao, Wen-Dong; Li, Xiao-Hui; Liu, Wenlong; Xue, Huai-Guo; Guo, Sheng-Ping
Abstract : Introduction of potassium into the structure of AgGaQ2 (Q = S, Se) brings a new nonlinear optical active selenide KAg3 Ga8 Se14 with a novel structure-type and balanced performance. Abstract : Obtaining fresh nonlinear optical (NLO) materials is an attractive and challenging topic for the development of laser techniques. Using benchmark AgGaQ2 (Q = S, Se) as the template, new KAg3 Ga8 Se14 is obtained by a solid-state reaction. Its structure can be built by the intergrowth of 2 : 1 AgGaSe2 and Ga2 Se3 -like slabs if the K site is occupied by Ag. Powdery KAg3 Ga8 Se14 demonstrates moderate phase-matchable NLO responses, and a LDT of ca. 2 × AgGaS2 . DFT calculations reveal that both AgSe4 and GaSe4 tetrahedral motifs contribute a lot to the NLO performance. This work reveals a new class of promising infrared NLO materials, and the design strategy may apply to other systems.